PEMODELAN PROSES BISNIS MANAJEMEN ASET MENGGUNAKAN TOGAF ARCHITECTURE DEVELOPMENT METHOD Studi Kasus: STMIK XYZ Surakarta - Sri Harjanto; Setiyowati Setiyowati (STMIK Sinar Nusantara, 2018)
STMIK XYZ is one of the universities in Surakarta. From the business process, there are some potential problems that interfere the asset inventory process as one of the asset management functions. To knowing some of the assets, its condition, and its position needs long time and also its data entry is less optimal. Purpose business architecture design and be able to integrate the main business activities using the TOGAF ADM framework. The existence of assets is a problem in the business process that runs on STMIK XYZ. It taken an architecture for the development of Information Systems, as well as the analysis and modeling of business processes so that the performance of institutions can realize the achievement of the objectives and it the improvement of business processes. This study uses Business Modeling Notation (BPMN) and TOGAF ADM methods to identify the needs and Business Process Reenginerin (BPR) in the development of information systems in households. The proposed this study was to make an asset management plan using the TOGAF ADM method.